SINEMA PASCANASIONAL: REPRESENTASI INDONESIA DALAM FILM-FILM GARETH EVANS - Abrian, Rizky; Sulistiawati, Afwin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The emergence of Indonesian films lately is not only initiated by Indonesian directors, but also foreign directors. Gareth Evans who is a director from Wales managed to attract the attention of Indonesian film audiences with his films. The phenomenon of foreign directors who created Indonesian films to become representations in the world of international film is something that needs to be studied further. This research is descriptive qualitative because the data, words and sentences, are analyzed based on meaning relations. In analyzing the data, researchers used representation theory and the theory of postnational film, namely by searching for Indonesian representations of what is contained in the film and identifying the condition of postnational films in Evans's films. From the results of the analysis, it was found that there was a representation of Indonesia in films by Evans. The aspect of representation that appeared consisted of several aspects: aspects of the language of communication used in the film, aspects of settings that were raised as the background, aspects of characters based on the names of characters, backgrounds of figures, and the use of silat as a fighting style. It also found the condition of postnational films in Evans’s films. Key word: films, representations, postnational